Plataforma interativa multimodal para reabilitação de déficit motor em crianças com deficiência do desenvolvimento - Silveira, Mariana Lyra (2019)
Children with Autism Spectrum Disorder, Down Syndrome, Cerebral Palsy, and Develop mental Coordination Disorder tend to have chronic motor disabilities associated with gait and manipulation. One of the factors that contribute to these deficits is a poor balance control, which is one of the main concerns of programs for balance rehabilitation focused on developmental disabilities. Although conventional therapy techniques present consistent and significant results, they offer repetitive physical tasks that can become monotonous and demotivating over time. An alternative way to foster high motivation and create positive emotional experiences is to use games developed for clinical purposes. This work presents the proposal and development of a multimodal platform of interactive games, which aims to assist balance rehabilitation. The results show that the proposed platform was able to promote the performance of lateral and posterior gait. Among the children who performed the experimental tests, even the youngest were able to understand the purpose of both games and complete the entire experimental protocol, indicating that the tool here described can be applied to an audience with an age group of three years old or more. It was found that one of the games had an average success rate of 95.7%, which is a excelent result. In addition, through the experimental tests, it was possible to verify that the proposed metrics for balance evaluation characterized the behavior of the participants, being possible to quantify their kinetic energy and their displacement within the room in which the experiments occurred. As for the motivational aspects, it is believed that the developed technology created positive emotional experiences, since 78% of the participants expressed the desire to continue playing even after the experimental protocol had ended.